2021
DOI: 10.1111/mec.16317
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow influences the genomic architecture of local adaptation in six riverine fish species

Abstract: Understanding how gene flow influences adaptive divergence is important for predicting adaptive responses. Theoretical studies suggest that when gene flow is high, clustering of adaptive genes in fewer genomic regions would protect adaptive alleles from among-population recombination and thus be selected for, but few studies have tested this hypothesis with empirical data. Here, we used RADseq to generate genomic data for six fish species with contrasting life histories from six reaches of the Upper Mississipp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 104 publications
2
33
0
3
Order By: Relevance
“…A highly polygenic, genotypically redundant (as in [29]) architecture can allow for LA to occur even when the alleles are individually prone to swamping by migration (hereafter: swamping-prone alleles; [27]). Therefore, the question remains as to whether genomes with multiple, large and old inversions involved in LA under high gene flow could be consistent with a highly polygenic architecture, and whether inversions could establish as a means of accumulation (as opposed to capture, as previous theory/simulations have assumed) of small-effect alleles [30].…”
Section: Introductionmentioning
confidence: 99%
“…A highly polygenic, genotypically redundant (as in [29]) architecture can allow for LA to occur even when the alleles are individually prone to swamping by migration (hereafter: swamping-prone alleles; [27]). Therefore, the question remains as to whether genomes with multiple, large and old inversions involved in LA under high gene flow could be consistent with a highly polygenic architecture, and whether inversions could establish as a means of accumulation (as opposed to capture, as previous theory/simulations have assumed) of small-effect alleles [30].…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal rearrangements, and inversions, in particular, are known to reduce effective recombination among alleles at different loci involved in local adaption, facilitating local adaptation under gene flow (Jones et al, 2012 ; Kirkpatrick & Barton, 2006 ; MĂ©rot et al, 2020 ). Using new sequencing approaches, an increasing number of empirical examples of rearrangements involved in local adaptation have been reported (Le Moan et al, 2021 ; Shi et al, 2021 ; Tepolt et al, 2022 ; Whiting et al, 2021 ). For instance, in the marine snail, Littorina saxatilis , polymorphism in several chromosomal inversions underlies major genetic differences between a large ecotype adapted to crab predation and a small ecotype adapted to wave action (Faria et al, 2019 ; Morales et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both theoretical simulation studies and empirical studies have shown that increased gene flow will lead to the increasingly concentrated genomic architecture of local adaptation (Shi et al, 2021 ; Via, 2012 ; Yeaman, 2013 ; Yeaman & Whitlock, 2011 ). In a species with high gene flow across heterogeneous environments, adaptive differentiation is often restricted to genomic islands of divergence that can resist the homogenizing effects of gene flow (Via, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…To estimate linkage disequilibrium (LD) of each candidate region, we calculated r 2 using PLINK v1.9 (‐‐ld‐window 999999999 ‐‐ld‐window‐kb 30000 ‐‐ld‐window‐r2 0.05) for SNPs with MAF ≄0.01 and located at least 400 bp from one another for each chromosome with a candidate region. We compared LD between pcadapt outliers within a candidate region and random SNPs (chromosomal background) on the same chromosome, visualized the differences using boxplots, and tested for significance using permutation tests with 10,000 iterations following the permutation test procedures described in Shi et al ( 2021 ). Briefly, this involved drawing 10,000 samples of random SNPs equal to the number of pcadapt outliers within the candidate region to generate the null distribution for that chromosome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation